Early Experience of Laparoscopic Colonic Surgery and its Associated Factors - Faiz Ur Rahman, Saadia Nawaz Durrani, Muhammad Zafar Iqbal, Mohammad Shoaib Khan, Kanwal, Malik Irfan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The research discusses the indications, tumour size, operational time, duration of analgesic required postoperatively, postoperative complications, recovery of bowel function and mortality associated with laparoscopic colonic surgery. Methods: This Case series studies were undertaken at the surgical department of DHQ Teaching Hospital, Rawalpindi and Bacha Khan Medical Complex, Swabi for duration of one year from 15th September 2020 to 15th September 2021. Clinical and operational data were collected from all laparoscopic-assisted colonic surgeries. Results: During this time, 85 laparoscopic-assisted colonic procedures were conducted. There were 76 carcinoma cases, 6 TB cases, and 3 polyp cases. From all, 60 cases were of right hemicolectomy, 12 cases of left hemicolectomy were performed, 5 cases of sigmoid colectomy were performed, 6 cases of segmental resection of splenic flexure were performed, and 2 cases of transverse colostomy were performed. Four cases were converted to open surgery due to locally advanced disease, one due to haemorrhage, and one due to failure to distinguish the tumour. The average time of the surgery was 140 minutes. The tumours were on average 5 cm in diameter. The average duration of analgesic use was 2.2 days. The average time for bowel activity to recover was 2.9 days, with a 6-day hospital stay. In one patient, traction injury to the small intestine occurred during surgery. Two patients got local wound infection after surgery, and two patients acquired lung infection. Conclusions: Colonic surgeries with laparoscopic assistance are linked with a smaller incision, a faster resumption of bowel activity, less painkiller use, a shorter hospital stay, and low incidence of pulmonary infection. Colon surgery may be performed laparoscopically and is an excellent first step toward obtaining advanced laparoscopic outcomes